Stunting, Perjalanan sejak Bayi Lahir Rendah dengan Pola Pemberian Makan - Salma Nur Fauziah; Titik Respati; Budiman (Bandung Conference Series: Medical Science, 2024)
Abstract. Low Birth Weight (LBW) has a stunting risk factor of 4.24 times compared to normal birth weight. Inadequate nutritional factors such as improper feeding patterns, can affect stunting. This study aimed to determine the relationship between LBW and feeding patterns with stunting in toddlers in the working area of Puskesmas Payungsari. This research method is an observational analysis with a quantitative approach. The design used is the control case. The number of respondents consisted of 51 stunted people and 51 non-stunted people. Univariate analysis to determine the picture of low birth weight and eating patterns aims to determine the characteristics of stunting toddlers based on low birth weight and feeding patterns. Furthermore, bivariate analysis was carried out using the Chi-square test. The percentage of LBW history is more found in stunted toddlers (39.22 and 3.92%) than in the non-stunting group. Improper diet in the stunting group was greater than in the non-stunting group (68.63 and 5.88%). There is a relationship between low birth weight and stunting (p<0.01; OR=15.81) and there was a relationship between feeding patterns and stunting (p<0.01; OR=35). In conclusion, the results of this study show that low birth weight and feeding patterns significantly increase the chances of stunting toddlers. The relationship between LBW variables and unidirectional eating patterns means that LBW is more prevalent in stunted toddlers, while the better the diet, the incidence of stunting will decrease. Therefore, it is necessary to educate parents about feeding patterns for toddlers. Abstrak. Berat Bayi Lahir Rendah (BBLR) memiliki faktor risiko stunting sebesar 4,24 kali dibandingkan dengan berat badan lahir normal. Faktor nutrisi yang tidak adekuat seperti pola pemberian makan yang tidak tepat dapat mempengaruhi stunting. Tujuan penelitian ini untuk mengetahui hubungan Berat Bayi Lahir Rendah (BBLR) dan pola pemberian makan dengan stunting pada balita di wilayah kerja Puskesmas Payungsari. Metode penelitian ini adalah analisis observasional dengan pendekatan kuantitatif. Desain yang digunakan adalah case control. Jumlah responden terdiri dari 51 orang stunting dan 51 orang tidak stunting. Analisis univariat untuk mengetahui gambaran BBLR dan pola makan yang bertujuan untuk mengetahui karakteristik balita stunting berdasarkan BBLR dan pola pemberian makan. Selanjutnya dilakukan analisis bivariat dengan menggunakan uji Chi square. Presentase riwayat BBLR lebih banyak ditemukan pada balita stunting (39.22 dan 3.92%) dibandingkan kelompok tidak stunting. Pola makan yang tidak tepat dalam kelompok stunting lebih besar dibanding kelompok tidak stunting (68.63 dan 5.88%). Terdapat hubungan antara BBLR dengan stunting (p<0,01; OR=15,81) dan terdapat hubungan pola pemberian makan dengan stunting (p<0,01; OR=35). Simpulan, hasil penelitian ini menunjukkan BBLR dan pola pemberian makan secara bermakna memiliki peluang lebih tinggi pada balita stunting. Hubungan antara variabel BBLR dan pola makan searah artinya BBLR lebih banyak terjadi pada balita stunting sedangkan semakin baik pola makan maka tingkat kejadian stunting akan berkurang. Oleh karena itu perlu mengedukasi mengenai pola pemberian makan kepada orang tua balita.